2006
DOI: 10.1007/s11262-006-0077-5
|View full text |Cite
|
Sign up to set email alerts
|

Expression of full-length and truncated Rep genes from Mungbean yellow mosaic virus-Vigna inhibits viral replication in transgenic tobacco

Abstract: Mungbean yellow mosaic virus-Vigna (MYMV-Vig) is a bipartite geminivirus that causes a severe yellow mosaic disease in blackgram. An assay was developed to study MYMV-Vig replication by agroinoculation of tobacco leaf discs with partial dimers of the virus. This assay, in a non-host model plant, was used to evaluate pathogen-derived resistance contributed by MYMV-Vig genes in transgenic plants. Viral DNA accumulation was optimum in tobacco leaf discs cultured for 10 days after infection with Agrobacterium tume… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
38
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 40 publications
(38 citation statements)
references
References 46 publications
0
38
0
Order By: Relevance
“…Alternatively, we found that tobacco (cv. Wisconsin 38) leaf discs, agroinoculated with the partial dimers of MYMV DNA A and DNA B, replicated and accumulated MYMV DNA A [29]. We raised transgenic tobacco plants with the candidate genes and used the tobacco leaf disc agroinoculation assay to evaluate the effect of transgenes on MYMV DNA accumulation.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Alternatively, we found that tobacco (cv. Wisconsin 38) leaf discs, agroinoculated with the partial dimers of MYMV DNA A and DNA B, replicated and accumulated MYMV DNA A [29]. We raised transgenic tobacco plants with the candidate genes and used the tobacco leaf disc agroinoculation assay to evaluate the effect of transgenes on MYMV DNA accumulation.…”
Section: Resultsmentioning
confidence: 99%
“…Three transgenic TrAP-DAD-tobacco plants which accumulated varying levels of the TrAP-DAD transcript and two VirE2-transgenic tobacco plants which complemented a virE2 mutation in Agrobacterium were evaluated for inhibition of MYMV DNA replication using the leaf disc agroinoculation assay [29]. The plants which accumulated higher levels of the TrAP-DAD and virE2 transcripts displayed a pronounced reduction in MYMV DNA accumulation.…”
Section: Introductionmentioning
confidence: 99%
“…Brunetti et al [36] also reported resistance in tomato plants against TYLCV using truncated Rep protein. Deletion of three motifs (conserved in all geminiviral AL1/AC1 protein) at N-and C-terminus may lead to the abolition of the role of DNA cleavage, ligation, ATP hydrolysis, and cell cycle regulation that will ultimately affect viral replication [7]. Out of four 5 0 AtC1 plant lines expressing first 210 amino acids of N-terminus, only one line gave reliable resistance.…”
Section: Discussionmentioning
confidence: 99%
“…Transgenic expression of pathogen-derived sequences has variously been explored and exploited the general idea that the expression of virus-derived selective sequences may interfere with the viral life cycle. The transgenic sequence can act via a protein-mediated mechanism or by post-transcriptional gene silencing (PTGS) resulting in virus tolerance [7][8][9]. Expression of Rep in sense orientation inhibited African cassava mosaic virus (ACMV) replication [10].…”
Section: Introductionmentioning
confidence: 99%
“…Collapse in degree of geminivirus resistance in various transgenic plants has also been reported. Failure or limited effectiveness of the RNAi based strategies has been highlighted in the case of MSV [33] and Mungbean yellow mosaic virus [34]. In these cases, full-length or truncated antisense Rep gene constructs were found to be ineffective in providing resistance.…”
Section: Emergence Of Relevant Techniques To Fight Against Geminivirusesmentioning
confidence: 99%